Faktor-faktor yang mempengaruhi Kepuasan Nasabah dalam Mengambil Kredit di PT. BPR Muatiara Nagari Sijunjung - Esi Sriyanti; Rasidah Nasrah; Alvina Mulyeni (Pusat Riset dan Inovasi Nasional, 2026)
This research intends to evaluate how service quality and credit procedures affect customer satisfaction during the application process for public transportation loans at PT BPR Mutiara Nagari Sijunjung. Utilizing a descriptive methodology paired wit+h a quantitative strategy, the study gathers primary data through questionnaires given to participants, employing a purposive sampling method, and includes a total of 48 customers in the sample. Results from the partial tests demonstrate that service quality positively influences customer satisfaction. This is supported obtained being greater than the critical t-value (3.054 > 2.01290), along with a significance level of 0.000, which is less than 0.05. In addition, the credit procedures also exhibit a favorable effect on customer satisfaction, with the t-value (2.603) surpassing the t-table value (2.01290) and a significance level of 0.012, which is under 0.05. Moreover, the F-test analysis shows the calculated F-value is 43.106, exceeding the F-table value of 3.20. This indicates that both service quality and loan processing together have a significant positive influence on customer satisfaction during the loan application process at PT BPR Mutiara Nagari Sijunjung.